Switzerland : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that the Swiss economy has returned to growth with supportive external demand and domestic policies. However, the recovery has been fragile, and business indicators suggest that activity is currently experiencing a soft patch. The IMF staff projects growth of 1u percent in 2005, from 1.7 percent in 2004, with some risks on the downside if demand from partner countries were to falter. Potential growth is estimated at 1 1\2 percent and is projected to decline in the medium term to 3/4 percent as a result of population aging.